THE INFLUENCE OF PSYCHOEMOTIONAL DISORDERS ON THE THICKNESS PARAMETERS OF THE INTIMA-MEDIA OF CAROTID ARTERIES AND TUMOR NECROSIS FACTOR-α IN YOUNG MEN WITH ARTERIAL HYPERTENSION - Bilovol, O.M.; Kniazkova, I.I.; Kіrienko, O.M.; Kuzminova, N.V.; Mishchenko, V.K.; Kіrienko, D.O.; Abramova, L.P. (World of Medicine and Biology, 2024)
The purpose of the study was to establish the peculiarities of changes in the parameters of the structural state of the common carotid arteries, as well as the content of tumor necrosis factor-α in blood serum depending on psycho-emotional status in young men with arterial hypertension. We examined 76 men (mean age 36.4±3.5 years) with grade 1 hypertension, including 55 patients with moderate and high anxiety (group 1) and no disorders of psychoemotional status (group 2). The control group consisted of 20 healthy men. It was established that in group 1, the levels of systolic and diastolic blood pressure during office measurement and daily monitoring exceeded (p
Keywords: arterial hypertension; psycho-emotional disorders; tumor necrosis factor-α; intima media complex